2013
DOI: 10.1007/s11010-013-1637-3
|View full text |Cite
|
Sign up to set email alerts
|

LPS induces cardiomyocyte injury through calcium-sensing receptor

Abstract: Calcium-sensing receptor (CaSR) belongs to the family C of G-protein coupled receptors. We have previously demonstrated that CaSR could induce apoptosis of cultured neonatal rat ventricular cardiomyocytes in simulated ischemia/reperfusion. It remains unknown whether the CaSR has function in lipopolysaccharide (LPS)-induced myocardial injure. The aim of this study was to investigate whether the CaSR plays a role in LPS-induced myocardial injury. Cultured neonatal rat cardiomyocytes were treated with LPS, with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…RIPK2 activates NF‐kappa‐β and induces cell death (McCarthy, Ni, & Dixit, ). Up‐regulation of CASR leads to apoptosis in rat myocytes exposed to LPS (Wang et al, ). To our knowledge, we are the first to report differential expression of RIPK2 and CASR in anthozoans.…”
Section: Discussionmentioning
confidence: 99%
“…RIPK2 activates NF‐kappa‐β and induces cell death (McCarthy, Ni, & Dixit, ). Up‐regulation of CASR leads to apoptosis in rat myocytes exposed to LPS (Wang et al, ). To our knowledge, we are the first to report differential expression of RIPK2 and CASR in anthozoans.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that injury to the rat myocardium induced by lipopolysaccharide is mediated by CaSR [15]. However, little is known about the role of CaSR in the formation of CaOx nephrolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [15] have reported that lipopolysaccharide-induced cardiomyocyte injury is related to CaSR-mediated OS and increases in the tumor necrosis factor- α (TNF- α ) and interleukin-6 (IL-6) levels. It remains unknown whether CaSR plays a role in CaOx-induced injury in cells and in animal models of urolithiasis.…”
Section: Introductionmentioning
confidence: 99%
“…These hypotheses list the formation of free oxygen radicals, lipid peroxidation, cytochrome P450 system induction, increase in intracellular calcium, increase in vasoconstrictor eicosanoid synthesis, and apoptosis. 1,[4][5][6] Free oxygen radical damage is the most frequently mentioned mechanism in the pathogenesis of CsAassociated organ toxicities. 1 Previously conducted studies have shown that it causes oxidative damage in the kidneys 1 and liver 7 and eventually an increase in lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%